Cystatin C Deficiency Increases LPS-Induced Sepsis and NLRP3 Inflammasome Activation in Mice - Monika Biasizzo; Mojca Trstenjak-Prebanda; Klemen Dolinar; Sergej Pirkmajer; Janja Završnik; Boris Turk; Nataša Kopitar-Jerala (Cells, 2021)
Cystatin C is a potent cysteine protease inhibitor that plays an important role in various biological processes including cancer, cardiovascular diseases and neurodegenerative diseases. However, the role of CstC in inflammation is still unclear. In this study we demonstrated that cystatin C-deficient mice were significantly more sensitive to the lethal LPS-induced sepsis. We further showed increased caspase-11 gene expression and enhanced processing of pro-inflammatory cytokines IL-1β and IL-18 in CstC KO bone marrow-derived macrophages (BMDM) upon LPS and ATP stimulation. Pre-treatment of BMDMs with the cysteine cathepsin inhibitor E-64d did not reverse the effect of CstC deficiency on IL-1β processing and secretion, suggesting that the increased cysteine cathepsin activity determined in CstC KO BMDMs is not essential for NLRP3 inflammasome activation. The CstC deficiency had no effect on (mitochondrial) reactive oxygen species (ROS) generation, the MAPK signaling pathway or the secretion of anti-inflammatory cytokine IL-10. However, CstC-deficient BMDMs showed dysfunctional autophagy, as autophagy induction via mTOR and AMPK signaling pathways was suppressed and accumulation of SQSTM1/p62 indicated a reduced autophagic flux. Collectively, our study demonstrates that the excessive inflammatory response to the LPS-induced sepsis in CstC KO mice is dependent on increased caspase-11 expression and impaired autophagy, but is not associated with increased cysteine cathepsin activity.